2022
DOI: 10.3389/fnut.2022.966790
|View full text |Cite|
|
Sign up to set email alerts
|

Approaching to biogenic amines as quality markers in packaged chicken meat

Abstract: Following the chicken meat quality decay remains a tricky procedure. On one hand, food companies need of fast and affordable methods to keep constant higher sensory and safety standards, on the other hand, food scientists and operators find difficult conjugating these exigencies by means of univocal parameters. Food quality definition itself is, in fact, a multi-layered and composite concept in which many features play a part. Thus, here we propose an index that relies on biogenic amines (BAs) evolution. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
1
8
1
Order By: Relevance
“…Notably, Rodriguez et al (2015) reported significantly different results, where the levels of all AA on the first day of storage exceeded those reported in other studies ( Lázaro et al, 2015 ). Furthermore, in contrast to the linear increase in BA content found in this study and other works ( Min et al, 2007a , b ; Triki et al, 2018 ; Nisar et al, 2019 ; Esposito et al, 2022 ), Lázaro et al (2015) and Rodriguez et al (2015) documented a linear decrease in the content of BA with storage time. In this study, on the first day of storage, the BAI index in both breast and leg muscles did not exceed 5 mg/kg, considered an appropriate level for fresh meat ( Ruiz-Capillas and Herrero, 2019 ; Wojcik et al, 2022) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Notably, Rodriguez et al (2015) reported significantly different results, where the levels of all AA on the first day of storage exceeded those reported in other studies ( Lázaro et al, 2015 ). Furthermore, in contrast to the linear increase in BA content found in this study and other works ( Min et al, 2007a , b ; Triki et al, 2018 ; Nisar et al, 2019 ; Esposito et al, 2022 ), Lázaro et al (2015) and Rodriguez et al (2015) documented a linear decrease in the content of BA with storage time. In this study, on the first day of storage, the BAI index in both breast and leg muscles did not exceed 5 mg/kg, considered an appropriate level for fresh meat ( Ruiz-Capillas and Herrero, 2019 ; Wojcik et al, 2022) .…”
Section: Discussioncontrasting
confidence: 99%
“…BA levels in the analyzed groups exhibited a linear increase during storage, aligning with similar findings reported by various authors ( Min et al, 2007a , b ; Sirocchi et al, 2013 ; Triki et al, 2018 ; Wen et al, 2020 ; Esposito et al, 2022 ). Comparable results were obtained by authors investigating BA levels in other meat types ( Fraqueza et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After this, 2 mL of acetone solution containing 20 mg of Dansyl chloride (Fluka) was added to the alkaline amine extract [ 18 ]. Derivatization was completed according to the protocol established by Esposito et al [ 19 ] without modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The preset conditions limit such as improper handling, improper transport, and lack of cold storage facilities can easily lead to chilled broiler meat oxidation and spoilage, which often generates volatile amines, BAs, organic acids, sulfides, alcohols, aldehydes, and ketones, which have unpleasant and unacceptable off-flavors [ 23 ]. Among them, BAs are often used as a characteristic marker for detecting chilled broiler meat spoilage [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%